2019
DOI: 10.4317/medoral.23105
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic characteristics are related to the advanced clinical stage of oral cancer

Abstract: Socio-demographic characteristics are related to the advanced clinical stage of oral cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
2
11
1
2
Order By: Relevance
“…Individuals diagnosed with oral cancer have a higher frequency of clinical stage IV ( 13 , 16 ), due to the late search for care, considering that initial injuries, in most cases, have no symptoms, being underestimated by the individual himself and by health professionals ( 15 ). Among these individuals, this study shows that men are the majority affected by stage IV cancer, as well as those who abuse of alcohol and tobacco, corroborating previous findings in the literature ( 1 , 8 , 13 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Individuals diagnosed with oral cancer have a higher frequency of clinical stage IV ( 13 , 16 ), due to the late search for care, considering that initial injuries, in most cases, have no symptoms, being underestimated by the individual himself and by health professionals ( 15 ). Among these individuals, this study shows that men are the majority affected by stage IV cancer, as well as those who abuse of alcohol and tobacco, corroborating previous findings in the literature ( 1 , 8 , 13 ).…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of oral cancer in Brazil is considered one of the highest in the world, with high rates of morbidity and mortality, which highlights its relevance in public health ( 1 - 3 ). Oral cancer is among the six most common types of cancer in males and among the eight most prevalent in females ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…This analysis revealed that cities with strong inequality in the income distribution have a higher risk of presenting hospitalized cases of oral cancer. Socioeconomically disadvantaged individuals are often diagnosed with lesions in advanced clinical stages and with cervical metastases, which require complex treatments performed in the hospital setting [ 8 , 16 ]. Previous studies that used regions and states as sample units found no association between the Gini coefficient and oral cancer rates [ 13 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other aspects such as human papillomavirus infection, solar radiation and genetics are also part of its complex etiology [ 2 , 5 , 6 ]. In addition, socioeconomic factors are strongly associated with the risk of oral cancer [ 7 , 8 ]. In general, individuals with worse socioeconomic status are more exposed to behavioral risk factors (such as tobacco and alcohol consumption) and have limited access to health services throughout their lives, which contributes to less prevention and late diagnosis of oral cancer [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation